A Rapid and Facile Approach for the Recycling of High‐Performance LiNi1−x−yCoxMnyO2 Active Materials. Issue 1 (10th September 2020) - Binder, Jan O.; Culver, Sean P.; Zeier, Wolfgang G.; Janek, Jürgen
Abstract: The demand for lithium‐ion batteries has risen dramatically over the years. Unfortunately, many of the essential component materials, such as cobalt and lithium, are both costly and of limited abundance. For this reason, the recycling of lithium‐ion battery electrodes is crucial to ensuring the availability of such resources and protecting the environment. Herein, a simple and scalable recycling process was developed for the prototypical cathode active material Li1.02 (Ni0.8 Co0.1 Mn0.1 )0.98 O2 (NCM‐811). By a combination of thermal decomposition and dissolution steps, spent NCM could be converted into Li2 CO3 and a transition metal oxalate blend, which served as precursors for new NCM. Importantly, it was also possible to individually separate each transition metal during the recycling process, thereby extending the utility of this method to a wide variety of NCM compositions. Each intermediate in the process was investigated by scanning electron microscopy and X‐ray diffraction. Additionally, the elemental composition of the recycled NCM‐811 was confirmed using inductively coupled plasma optical emission spectroscopy and energy‐dispersive X‐ray spectroscopy. The electrochemical performance of the recycled NCM‐811 exhibited up to 80 % of the initial capacity of pristine NCM‐811. The method presented herein serves as an efficient and environmentally benign alternative to existing recycling methods for lithium‐ion battery electrode materials. Abstract : Recycle and re‐synthesize : Spent LiNi0.8 Co0.1 Mn0.1 O2 (NCM‐811) from Li‐ion batteries is recovered by a facile and inexpensive recycling approach. After a series of decomposition and dissolution reactions, Ni/Co/MnC2 O4 and Li2 CO3 are formed, which serve as precursors for the re‐synthesis of NCM‐811. Additionally, the individual separation of the transition metal compounds is possible.